A Quantitative and Rapid Knoevenagel Condensation Catalyzed by Recyclable Zeolite Imidazole Frameworks. Issue 4 (25th January 2019) - Kumar, Nandigama Satish; Reddy, Marri Sameer; Kumar, S. Tirumala Santosh; Bheeram, Vema Reddy; Mukkamala, Saratchandra Babu; Rao, L. Chandrasekhara
Abstract: We here report a comparative study on catalytic application of ZIF‐8 and ZIF‐67 for the Knoevenagel condensation of diverse isatins/indeno[1, 2‐b]quinoxalin‐11‐nones with malononitrile, quantitatively. Good to excellent yields of product in analytically pure form were isolated without using column chromatography. The presented method was successfully scaled up to gram scale and the catalyst was reused up to 4 successive cycles without considerable loss in its catalytic efficiency. Abstract : We here report a comparative study on catalytic application of ZIF‐8 and ZIF‐67 for the Knoevenagel condensation of diverse isatins/indeno[1, 2‐b]quinoxalin‐11‐nones with malononitrile, quantitatively. Good to excellent yields of product in analytically pure form were isolated without using column chromatography. The presented method was successfully scaled up to gram scale and the catalyst was reused up to 4 successive cycles without considerable loss in its catalytic efficiency.